2019
DOI: 10.3390/cells8020176
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Androgen Receptor Signaling in Ovarian Cancer

Abstract: Emerging evidence has suggested that androgen receptor signaling plays an important role in ovarian cancer outgrowth. Specifically, androgen receptor activation appears to be associated with increased risks of developing ovarian cancer and inducing tumor progression. However, conflicting findings have also been reported. This review summarizes and discusses the available data indicating the involvement of androgens as well as androgen receptor and related signals in ovarian carcinogenesis and cancer growth. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 109 publications
2
43
0
1
Order By: Relevance
“…In a Phase II study of single agent enzalutamide in AR positive recurrent ovarian cancer ≥ 5% AR expression by IHC was considered positive [20]. The activation of AR leads to its nuclear localization and regulation of expression of genes involved in different physiological and pathological functions [21]. AR signalling has been associated with tumorigenesis and metastasis of cancers such as prostate, bladder, kidney, lung, breast, liver and ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Phase II study of single agent enzalutamide in AR positive recurrent ovarian cancer ≥ 5% AR expression by IHC was considered positive [20]. The activation of AR leads to its nuclear localization and regulation of expression of genes involved in different physiological and pathological functions [21]. AR signalling has been associated with tumorigenesis and metastasis of cancers such as prostate, bladder, kidney, lung, breast, liver and ovary.…”
Section: Discussionmentioning
confidence: 99%
“…AR signalling has been associated with tumorigenesis and metastasis of cancers such as prostate, bladder, kidney, lung, breast, liver and ovary. Androgens have been shown to involved in cell proliferation and invasion of ovarian cancer cells suggesting targeting AR as a capable treatment choice [21,22]. AR targeted therapies have been widely employed in breast and prostate cancers [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…[3] Although with significant advances in the treatment, ovarian cancer still represents high mortality due to the asymptomatic behavior and advanced stage at diagnosis. [4] The 5-year survival rate is unfavorable in individuals with high-grade serous ovarian carcinoma, and therefore, early-stage detection may significantly decrease the death rates. [5] Currently, the detecting methods for ovarian cancer include biomarkers and transvaginal ultrasonography.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is a devastating gynecological malignant tumour, disturbing approximate 2-3% of women all over the world [1]. Even though substantial improvements have been undertaken for management approaches, ovarian cancer still characterises high mortality [2]. It has been reported that the 5-year survival rates are still below 45% due to the asymptomatic behaviour and the advanced stage at diagnosis [3].…”
Section: Introductionmentioning
confidence: 99%